If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 7 = 7 + 13 Reorder the terms: 7 + 9x = 7 + 13 Combine like terms: 7 + 13 = 20 7 + 9x = 20 Solving 7 + 9x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 9x = 20 + -7 Combine like terms: 7 + -7 = 0 0 + 9x = 20 + -7 9x = 20 + -7 Combine like terms: 20 + -7 = 13 9x = 13 Divide each side by '9'. x = 1.444444444 Simplifying x = 1.444444444
| y=30-2x | | -6[6x-(4x+8)]=9+(6x+3) | | 20/x=5 | | 20/z=5 | | 5(x+4)-10=5+4(x-1) | | 4/x=x+3 | | 2x+7y-y-x= | | ax-bx=8 | | 5m+6n+2m-n= | | 6y-10-3y+8=0 | | 3x+3=0.5x-2 | | -6v+13=1-8v | | 12+8q=13+7q | | -2=-x-2 | | -6+13=1-8v | | 5x+15+5y=10x | | -2x+8x+7y=49 | | -x/2=20 | | -4=-x-2 | | 4(70-2y/3)+3y=300 | | 3(5)=6(x+3) | | 4x+3y=300 | | 3z^2-2x^2=-6y | | 4(2x+7)=2x+25+3 | | 3x+2y=210 | | 3a+3a= | | x(4x-5)-(2x-7)(3x+2)= | | -x+4=2x+4 | | 2x+3=1-6(x-1) | | (2a^1/4)^3 | | 12x-4-(8x+3)+7x-2=68 | | 2/5w-7/5w=6 |